2009 International Conference on Mechatronics and Automation 2009
DOI: 10.1109/icma.2009.5246102
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of hand grasp force based on forearm surface EMG

Abstract: In the force control of multi-functional prosthetic hands, it is important to extract grasp force information besides mode specifications directly from the myoelectric signals. In this paper, a force sensor is adopted to record the hand's enveloping force when the hand is performing several grasp modes, synchronously with 6 channels surface electromyography (EMG) which are extracting from the subject's forearm. Three pattern regression methods, locally weighted projection regression (LWPR), artificial neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Grasping force estimation lies on the basis of force prediction in [35], which utilises the EMG signals to fit the exerted force. The model was tuned by the locally captured data of ten subjects.…”
Section: B Functional Module Descriptionmentioning
confidence: 99%
“…Grasping force estimation lies on the basis of force prediction in [35], which utilises the EMG signals to fit the exerted force. The model was tuned by the locally captured data of ten subjects.…”
Section: B Functional Module Descriptionmentioning
confidence: 99%
“…Mobasser et al [4] used multilayer perceptron ANN for hand force estimation from surface EMG signals for applications in sports activities. Yang et al [5] demonstrated the use of ANN, Locally Weighted Projection Regression (LWPR) and SVM to estimate hand grasp force from surface EMG signals for force control of multi-functional prosthetic hands. In this work, we propose an idea of estimating force from the surface EMG signals using a feed-forward ANN in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Marta et al (2012) developed a valid biomechanical model with artificial neural networks to compute the grasping posture related to handgrip force; artificial neural networks enhanced the model capability. Yang et al (2009) presented an efficient grip force prediction using support vector machine (SVM) when different hand fingers performed several grasp modes synchronously with six sEMG channels from the participants forearm. Mojgan (2010) investigated whether multi-class SVM could effectively predict hand orientation and torque from myoelectric signals when the wrists radial and ulnar deviations were increased gradually.…”
Section: Introductionmentioning
confidence: 99%